Cat rabies in Brazil: a growing One Health concern - de Lima, Jonathan Santos; Mori, Enio; Kmetiuk, Louise Bach; Biondo, Leandro Meneguelli; Brandão, Paulo Eduardo; Biondo, Alexander Welker; Maiorka, Paulo César (Frontiers in Public Health, 2023)
This review of human and cat rabies from 1986 to 2022 has shown mostly AgV3 variant in human cases with 29/45 (64.4%) reports including 23 from bats, four from cats, and two from unknown species, followed by 8/45 (17.8%) of AgV2 variant (all from dogs), 4/45 from marmoset variant (all from Callithrix jacchus), 2/45 samples compatible with wild canid variant (both from Cerdocyon thous), and one/45 of AgV1 variant from a domestic dog. Only one sample of human rabies was not typified, related to bat aggression. In addition, surveillance conducted in the state of São Paulo confirmed the presence of rabies in 7/23,839 cats (0.031%) and 3/106,637 dogs (0.003%) between 2003 and 2013, with a 10:1 overall cat-to-dog positivity ratio. This 10-fold higher infection rate for cat rabies may be explained by cats’ hunting habits and predation. In addition, after 28 years of rabies-free status, a new cat rabies case was reported in the city of São Paulo in 2011. The rabid cat lived, along with other pets, in a household located near the largest downtown city park, whose owners presented animal hoarding behavior. Thus, animal hoarders and rescuers, public health agents, animal health professionals, and the general population with contact need to be aware of the risk of bat-borne rabies followed by spillover from cats to humans. In conclusion, cat rabies cases are becoming increasingly important in Brazil. This poses a One Health concern, given the overlapping of human, bat and cat populations within the same predisposed environment.